Analysis Influence of Mother's Behavior, Socio-Economic, and Physical Home Environment - Putri, Dara Maulidya; Girsang, Ermi; Nasution, Sri Lestari (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Indonesia as a developing country is still facing this problem. It is very important to understand the related factors that influence several economic and environmental factors in the regulation of health conditions in Indonesia to find out which programs are more effective. Eco-nutrition has three main areas: public health (access to quality water, sanitation, and health services), socioeconomic (livelihood assets), and malnutrition. This study describes the relationship between socioeconomic factors and public health with malnutrition, stunting, and underweight in Indonesia. Data on the prevalence of malnutrition, stunting, wasting, education level, and public health factors (access to clean water, clean living behavior, utilization of posyandu, complete immunization coverage, the incidence of diarrhea, and incidence of acute respiratory infection (ARI) were obtained from previous research studies. socioeconomic status (poverty level and GRDP/capita) obtained from the Central Statistics Agency (BPS).